Cardiac beriberi and malnutrition: rare complication of paracoccidioidomycosis - Belda, Walter; Carvalho, Caroline H. C.; Franciozi, Amithis B.; Urresta, Carlos G. S.; Lee, Tiffany Y. H.; Nico, Marcello M. S. (International Journal of Research in Medical Sciences, 2023)
Paracoccidioidomycosis is an endemic systemic mycosis that predominates in southern Mexico, parts of Central America, and South America. It is caused by a dimorphic fungus and is generally acquired through the lungs, from where it disseminates. Paracoccidioidomycosis has different clinical manifestations that require differentiation with tuberculosis, Hodgkin disease, several systemic and subcutaneous mycoses, and squamous cell carcinoma. Radiologic abnormalities in the lung fields may be seen. Mucous membrane lesions occasionally occur. The diagnosis is confirmed by finding yeast-like elements of P. brasiliensis in microscopic examinations of wet preparations of specimens submitted for mycologic studies. The occurrence of malnutrition and particularly beri beri conditions concomitant with paracoccidioidomycosis is uncommon. We report a case of a patient of low socio-economic status, without permanent employment , possibly carrying out work as a bricklayer or working on small farms during the harvest season, with a five-year history of oral cavity lesions, which resulted in difficulty eating and thus weight loss. A diagnosis of paracoccidioidomycosis was made through direct microscopy examination, culture and multisystem involvement was confirmed through imaging tests, including dilatation and dysfunction of the right ventricle. The hypothesis of Cardiac Beri-Beri related to thiamine deficiency was raised. The treatment was carried out with thiamine supplementation and liposomal amphotericin B, with excellent clinical evolution of the patient. This case highlights the importance of early recognition of paracoccidioidomycosis in its early stages and the adoption of proactive measures in the search for possible organic complications caused by nutritional deficiencies in prolonged cases.